Immunogenicity of pandemic influenza A H1N1/2009 adjuvanted vaccine in pediatric solid organ transplant recipients. (20th May 2013) - Gavaldà, J.; Cabral, E.; Perez‐Romero, P.; Len, O.; Aydillo, T.; Campins, M.; Quintero, J.; Peghin, M.; Nieto, J.; Charco, R.; Pahissa, A.; Cordero, E.; et al.
Abstract The aim of this study was to assess the immunogenicity of a vaccine against this virus in a prospective cohort of transplanted pediatric patients without previous influenza infection who received one dose of MF59®‐adjuvanted pandemic H1N1/2009 vaccine. Seventeen patients who were being regularly followed up at the Outpatient Clinic of the Children's Transplant Unit (liver and kidney transplantation) in Hospital Universitari Vall d′Hebron (Barcelona) were included. Seroconversion was demonstrated in 15 of 17 (88.2%) vaccinated children. There were no rejection episodes or major adverse events. The MF59®‐adjuvanted pandemic H1N1/2009 vaccine was safe and elicited an adequate response.